Pelatihan Pembuatan Product Catalog Pada UMKM Kali Kepiting Sejahtera Kelurahan Pacar Kembang Kota Surabaya - Lailatul Amanah; Nur Handayani; Susanti Susanti; Dewi Mutmainnah; Nenny Syahrenny (JAST : Jurnal Aplikasi Sains dan Teknologi, 2025)
The Kali Kepiting Sejahtera MSME Association in Surabaya faces challenges, including a lack of professional product catalogs, limited managerial skills, and traditional and unstructured promotional methods. This community service activity aims to empower MSMEs through training in creating professional product catalogs, both printed and digital, accompanied by individual mentoring. The activity methods include providing basic product catalog materials, design training using simple applications, individual mentoring, and evaluation of catalog improvements. The main work is a collective and individual catalog product ready to be used for promotions, activity reports, journal publications, and PKM seminars. The work review indicates that this training enhances the ability of MSME managers to compile content and design catalogs, strengthen their business image, and provide structured promotional media. The impact of the activity is evident in the increased understanding of branding and digital promotion among participants, enhanced catalog operational capabilities, and MSME readiness to capitalize on opportunities for collaboration and new markets. The conclusion of the activity stated that 100% of MSME Kali Kepiting Sejahtera participants successfully created digital and printed product catalogs, both individually and collectively. The activity also succeeded in enhancing digital literacy, design skills, and understanding of product branding, in line with the initial needs of partners to improve their business promotion strategies.ABSTRAKPaguyuban UMKM Kali Kepiting Sejahtera di Surabaya menghadapi masalah belum tersedianya katalog produk profesional, keterampilan pengelola terbatas, serta promosi yang masih tradisional dan kurang terstruktur. Kegiatan pengabdian ini bertujuan memberdayakan UMKM melalui pelatihan pembuatan katalog produk profesional, baik cetak maupun digital, disertai pendampingan individual. Metode kegiatan meliputi pemberian materi dasar product catalog, pelatihan desain menggunakan aplikasi sederhana, pendampingan individual, dan evaluasi penyempurnaan katalog. Karya utama berupa produk katalog kolektif dan individual yang siap digunakan untuk promosi, laporan kegiatan, publikasi jurnal, dan seminar PKM. Ulasan karya menunjukkan bahwa pelatihan ini meningkatkan kemampuan pengelola UMKM dalam menyusun konten dan mendesain katalog, memperkuat citra usaha, serta memberikan media promosi yang terstruktur. Dampak kegiatan terlihat pada peningkatan pemahaman peserta mengenai branding dan promosi digital, kemampuan operasional katalog, serta kesiapan UMKM menghadapi peluang kerja sama dan pasar baru. Kesimpulan kegiatan menyatakan bahwa sebanyak 100% peserta UMKM Kali Kepiting Sejahtera berhasil membuat Product Catalog digital dan cetak, baik dalam bentuk individual maupun kolektif. Kegiatan juga berhasil meningkatkan literasi digital, kemampuan desain, dan pemahaman branding produk, sesuai dengan kebutuhan awal mitra dalam memperbaiki strategi promosi usaha.